Respuesta :

leena

Hey there! :)

Answer:

[tex]f^{-1}(x)[/tex] = ± [tex]\sqrt{\frac{1}{5}(x-2) }[/tex]

Step-by-step explanation:

Given:

f(x) = 5x² + 2

Switch the x and y variables in the equation:

x = 5y² + 2

Subtract 2 from both sides:

x - 2 = 5y²

Divide 5 from both sides:

[tex]\frac{1}{5}(x-2) = y^{2}[/tex]

Square root both sides:

y = ± [tex]\sqrt{\frac{1}{5}(x-2) }[/tex]

**Make sure to add a ±  sign when finding the inverse of a parabolic function.

Therefore, the inverse of this function is:

[tex]f^{-1}(x)[/tex] = ± [tex]\sqrt{\frac{1}{5}(x-2) }[/tex]